TF-ChIP Method for Tissue-Specific Gene Targets - Perna, Amalia; Alberi, Lavinia Auber (Frontiers in Cellular Neuroscience, 2019)
Chromatin immunoprecipitation (ChIP) is an assay developed in order to deﬁne the dynamic nature of transcription processes. This method has been widely employed to identify methylated and acetylated DNA sequences in a variety of organs both in animals and humans. Nevertheless, this technique is significantly less employed to study transcriptional targets of specific nuclear signaling factors (TF) and the data published so far has mainly used cell culture material and has been hardly reproduced in ex-vivo tissue. As nuclear signaling underlies important adaptive responses in chronic conditions such as cancer and neurodegeneration, which contribute to the progression of the disease, there is a need for streamlining the upfront workflow of TF-ChIP for subsequent target sequencing. Based on the typical low concentration of the signaling transcriptional complex and the complexity/length of the ChIP Seq protocol, the field of cellular signaling has been confronted with a major roadblock in identifying clinically relevant targets of pathological and physiological signaling pathways. The present protocol offers a standardized procedure for detecting signaling targets in any whole tissue or specific dissected regions. The advantages of the protocol as compared to the existing published methods are: 1) the small amount of starting material; appropriate for tissue subregions; 2) the optimization of DNA fragmentation from whole tissue; 3) suitability for sparsely populated tissues (i.e. brain); 4) the specificity of the TF-targeting readout and 5) high DNA quality for sequencing or hybridization.. The present protocol is highly detailed and can be reproduced using both fresh and fresh-frozen tissue. This is particularly relevant in the clinical setting, where specimen integrity is often the limiting step and where transcriptional target profiling is therapeutically relevant. The method is centered on Notch signaling but can be applied to a variety of nuclear signaling pathways as long as specific antibodies are available for pull down. Taken the superior yield/readout of this procedure, ChIP may finally provide relevant information about dynamic downstream gene changes in vivo for use in both basic research and clinical applications.